Physical activity patterns associated with a pedagogical intervention in six to eight year old children in an urban school - Germán Briceño; María Alejandra Prieto; Camilo Povea; Zorayda Moreno; Jaime Céspedes (Cogent Education, 2019)
This study evaluated changes in energy expenditure in six to eight-year-old children after a two year pedagogical intervention on healthy habits. Methods: This was a longitudinal descriptive observational study in children at a private school in Bogotá. Outcomes: change in the average energy expenditure(Kcal/day) and time dedicated to physical activity. The children’s physical activity(PA) was objectively assessed for six days using a multi-sensor device(Actiheart®). Results: A total of ten girls (52.63%) and nine boys (47.37%) were included. At the end of the follow-up, the energy expenditure had increased by 457.30 Kcal/day (p < 0.001), activities requiring <1.5 MET had decreased by 237.40 minutes (p < 0.001), and physical activity between 3–6 MET had increased by 88.90 minutes(p = 0.001). Conclusions: Children decreased their sedentary lifestyle and increased energy expenditure and physical activity, suggesting a possible change in them as a consequence of the intervention.